Peru : Selected Issues. (IMF Staff Country Reports; Country Report, 1998)
This Selected Issues paper reviews economic developments in Peru during 1995-98. In July 1996, the Executive Board of the IMF approved a follow-up extended arrangement in support of Peru's program for 1996-98. After a slowdown in 1996, economic activity picked up in 1997 while inflation declined significantly. The net official international reserves position strengthened further, and gross reserves reached the equivalent of close to eight months of imports of goods and services at end-1997. During 1996-97, Peru restructured the debt owed to foreign commercial and Paris Club bilateral creditors.